Physico-chemical analysis of molten electrolytes - Danek, Vladimir (Elsevier, 2006)
Physico-Chemical Analysis of Molten Electrolytes includes selected topics on the measurement and evaluation of physico-chemical properties of molten electrolytes. It describes the features, properties, and experimental measurement of different physico-chemical properties of molten salt systems used as electrolytes for different metal production, metallic layer deposition, as a medium for reactions in molten salts. The physico-chemical properties such as phase equilibria, density (molar volume), enthalpy (calorimetry), surface tension, vapor pressure, electrical conductivity, viscosity, etc. are the most important parameters of electrolytes needed for technological use. For each property the theoretical background, experimental techniques, as well as examples of the latest knowledge and the processing of most important salt systems will be given. The aim of Physico-Chemical Analysis of Molten Electrolytes is not only to present the state of the art on different properties of molten salts systems and their measurement, but also to present the possibilities of modeling molten salt systems, to be able to forecast the properties of an electrolyte mixture from the properties of the pure components in order to avoid experimentally demanding, and in most cases also expensive measurements. This book fills a substantial gap in this field of science. Also documententing the latest research in molten salts chemistry and brings new results and new insights into the study of molten salts systems using the results of X-ray diffraction and XAFS methods, Raman spectroscopy, and NMR measurements. * This book fills a substantial gap in this field of science * Serves as a invaluable reference for all people working in the field of molten salts chemistry * Describes fundamentals of the various properties of molten electrolytes.